Patients' Perceptions of Quality of Care: A Teamwork Intervention Study in a Surgical Ward - Marie Louise Hall-Lord PhD, RNT; Randi Ballangrud PhD, RNT (SAGE Publishing, 2022)
Introduction Improving teamwork competencies among health care professionals is important for patient safety. Few previous studies have investigated whether a teamwork intervention has an impact on patients' perceptions of quality of care. Objective To investigate patients' perceptions of quality of care before and after the implementation of a team training program in a surgical ward. Methods A quasi-experimental pre- and posttest design was used. The TeamSTEPPS ® team training program was implemented in a surgical ward. Three groups of consecutively sampled patients responded to the Quality from the Patient's Perspective (QPP) questionnaire including four dimensions with 25 items. In addition to the QPP, six items were developed for this study. In total, 223 patients responded to the questionnaire. The mean age was 59.6 years, and there were 128 males and 94 females. Results The physical-technical condition dimension and four items showed significantly higher scores after six months of intervention. The majority of the patients scored quality of care in the four dimensions as very high at all three time points. Younger patients reported the lowest care quality. Conclusion The results in this study indicate that the teamwork intervention had a minimal impact on the patients' perceptions of quality of care, with only significant differences between baseline and six months of intervention in one dimension and three items. At each data collection time point, the numbers of patients who perceived quality of care as modest decreased slightly. Younger patients were more likely to perceive care quality as modest.